الأسس التصميمية لفراغات لعب الأطفال في الحدائق العامة ( حالة دراسية مدينة دمشق ) - خضرة سجا (Latakia University Journal -Engineering Sciences Series, 2017)
اللعب حقّ لجميع الأطفال وهو نشاط هام في حياتهم ، يكتشفون من خلاله العالم المحيط بهم ، ولقد أكدّ الفلاسفة و علماء النفس والمربون على أهميته في حياة الأطفال وسلوكهم ونموهم ، لذلك يجب توفير فراغات للعب الأطفال أينما وجودوا ، وبشكل خاص ضمن الحدائق العامة ، ويجب أن تحظى بالاهتمام والدراسة الكافية وفق الأسس التصميمية العالمية ، بحيث تحقق للأطفال المتعة والفائدة معاً. يقدم البحث دراسة تحليلية لعدد من فراغات لعب الأطفال في الحدائق العامة في مدينة دمشق بهدف التحقق من مدى تلبية عناصرها المعمارية لحاجات الأطفال الترفيهية والتنموية ، من مختلف الفئات العمرية ، وذلك من خلال تحليل العناصر التصميمية للعينات المدروسة وتقييمها وفق المعايير الموصى بها . Playing is right for all children , and it’s an important activity in their life, they discover through it the world around them, and it was confirmed by philosophers, psychologists and educators on the importance in children’s lives and in their behavior and development. So we must provide spaces for children to play wherever they are, especially in public parks, and must be given adequate attention and study according to international design foundations, so check for children fun and interest together. The research presents an analytical study of some of the children’s playing spaces in parks in the city of Damascus in order to verify the extent to which architectural elements to the needs of recreational and development of children, from different age groups, and through the analysis of the design elements of the samples studied and evaluated in accordance with the recommended standards.